To factor the perfect square trinomials, we will determine if they can be expressed in the form \((a+b)^2\) or \((a-b)^2\).
- \(x^2 + 6x + 9\)
To factor this: \[ x^2 + 6x + 9 = (x + 3)^2 \]
- \(x^2 + 10x + 25\)
To factor this: \[ x^2 + 10x + 25 = (x + 5)^2 \]
- \(9x^2 + 12x + 4\)
To factor this: \[ 9x^2 + 12x + 4 = (3x + 2)^2 \]
- \(9x^2 - 30x + 25\)
To factor this: \[ 9x^2 - 30x + 25 = (3x - 5)^2 \]
So, summarizing the factors:
-
\(x^2 + 6x + 9 = (x + 3)^2\)
-
\(x^2 + 10x + 25 = (x + 5)^2\)
-
\(9x^2 + 12x + 4 = (3x + 2)^2\)
-
\(9x^2 - 30x + 25 = (3x - 5)^2\)